Maintenance-Ready Web Application Development - Ion IVAN; Narcis-Cosmin LUCA; Mihai Liviu DESPA; Eduard BUDACU (Informatică economică, 2016)
The current paper tackles the subject of developing maintenance-ready web applications. Maintenance is presented as a core stage in a web application’s lifecycle. The concept of maintenance-ready is defined in the context of web application development. Web application maintenance tasks types are enunciated and suitable task types are identified for further analysis. The research hypothesis is formulated based on a direct link between tackling maintenance in the development stage and reducing overall maintenance costs. A live maintenance-ready web application is presented and maintenance related aspects are highlighted. The web application’s features, that render it maintenance-ready, are emphasize. The cost of designing and building the web-application to be maintenance-ready are disclosed. The savings in maintenance development effort facilitated by maintenance ready features are also disclosed. Maintenance data is collected from 40 projects implemented by a web development company. Homogeneity and diversity of collected data is evaluated. A data sample is presented and the size and comprehensive nature of the entire dataset is depicted. Research hypothesis are validated and conclusions are formulated on the topic of developing maintenance-ready web applications. The limits of the research process which represented the basis for the current paper are enunciated. Future research topics are submitted for debate.